Evolution of salt tolerance in a laboratory reared population of C hlamydomonas reinhardtii - Marie‐Mathilde Perrineau; Ehud Zelzion; Jeferson Gross; Dana C. Price; Jeffrey Boyd; Debashish Bhattacharya (Environmental Microbiology, 2014)
Summary Understanding the genetic underpinnings of adaptive traits in microalgae is important for the study of evolution and for applied uses. We used long‐term selection under a regime of serial transfers with haploid populations of the green alga C hlamydomonas reinhardtii raised in liquid TAP medium containing 200 mM NaCl . After 1255 generations, evolved salt ( ES ) populations could grow as rapidly in high salt medium as progenitor cells (progenitor light [ PL] ). Transcriptome data were analysed to elucidate the basis of salt tolerance in ES cells when compared with PL cells and to cells incubated for 48 h in high salt medium (progenitor salt [ PS] , the short‐term acclimation response). These data demonstrate that evolved and short‐term acclimation responses to salt stress differ fundamentally from each other. Progenitor salt cells exhibit well‐known responses to salt stress such as reduction in photosynthesis, upregulation of glycerophospholipid signaling, and upregulation of the transcription and translation machinery. In contrast, ES cells show downregulation of genes involved in the stress response and in transcription/translation. Our results suggest that gene‐rich mixotrophic lineages such as C . reinhardtii may be able to adapt rapidly to abiotic stress engendered either by a rapidly changing climate or physical vicariance events that isolate populations in stressful environments.

Monoxenic nodulation process of Acacia mangium (Mimosoideae, Phyllodineae) by Bradyrhizobium sp - Marie-Mathilde Perrineau; Antoine Galiana; Sergio M. de Faria; Gilles Bena; Robin Duponnois; Paul Reddell; Yves Prin (Symbiosis, 2012)

Molecular phylogeny of Pisolithus species from Moroccan forest woodlands - Salah Eddine Bakkali Yakhlef; Daniel Mousain; Robin Duponnois; Marc Ducousso; Abdellatif Belkouri; Benaissa Kerdouh; Marie-Mathilde Perrineau; Mohamed Abourouh (Symbiosis, 2009)